HLA-DQ polymorphisms modify the risk of thyroid autoimmunity in children with type 1 diabetes mellitus - Sumník, Z; Drevínek, P; Snajderová, M; Kolousková, S; Sedláková, P; Pechová, M; Vavrinec, J; Cinek, O (Journal of pediatric endocrinology & metabolism, 2003)
OBJECTIVE: Type 1 diabetes mellitus (DM1) is frequently accompanied by thyroid autoimmunity (TAI). The aims of the present study were to estimate the prevalence of TAI and to determine the contribution of HLA-DQA1 and -DQB1 polymorphisms to TAI susceptibility among children with DM1. PATIENTS AND METLHODS: Screening for TAI was performed in 285 children with DM1 by measuring autoantibodies against thyroid peroxidase (anti-TPO) and thyroglobulin (anti-Tg). HLA-DQA1 and -DQB1 were genotyped using PCR-SSP. RESULTS: Repeated positivity of anti-TPO and/or anti-Tg was found in 45/285 children with DM1 (15.8%). The prevalence was significantly higher in girls than in boys (26.7% vs 6.7%; p<10(-5)). The HLA-DQB1*0302 allele conferred susceptibility to TAI in children with DM1 (OR 2.7, 95% CI 1.1-6.4), while the DQB1*05 alleles acted protectively (OR 0.2, CI 95% 0.08-0.7). CONCLUSIONS: HLA-DQ polymorphisms significantly modify the risk of TAI in children with DM1.
Keywords: autoimunitní tyreoiditida; Autoantibodies; alely; Infant; Humans; kojenec; dítě; polymorfismus genetický; Child; Female; Polsko; Phenotype; testy funkce štítné žlázy; Alleles; lidé; Poland; Polymorphism, Genetic; předškolní dítě; diabetes mellitus 1. typu; testování histokompatibility; Thyroiditis, Autoimmune; ženské pohlaví; Male; autoprotilátky; HLA-DQ Antigens; fenotyp; Adolescent; Thyroid Function Tests; HLA-DQ antigeny; Histocompatibility Testing; Risk Assessment; mužské pohlaví; Child, Preschool; hodnocení rizik; Diabetes Mellitus, Type 1; mladiství